224 - THE IMPORTANCE OF PLAYING AND PLAYING IN THE INITIAL SERIES (Fiep Bulletin - online, 2011)
The Game and the trick are important elements for the initial series in the school. The game is a physical or mental, voluntary activity, regard, that in it allows them to be outside of the reality. The game requires motor and cognitive abilities becoming more easy the development of the children, making with that they learn to take decisions and they make immediate choices. The game can be made in diverse places with different materials. The game and the trick are important because they in agreement contemplate different ages with definitive levels of requirement and as content collaborate to be passed of generation in generation thus contributing for the stronger of the culture. The game, in this society where we live, is seen as of small account, without value, considered as pastime or loss of time. The games and the tricks are traditional and each time more comes losing space in our society for the electronic games that many of the times alone stimulate the cognitive development leaving to stimulate the motor development.  The game and the guided trick help the child in some ways, develop its capacity to decide problems, allow to demonstrate its personalities, like, to exert its initiative, responsibility and to work cooperatively and collectively. This work aims at to know the importance of the game and the trick organized in the initial series of basic education to argue possibilities of education for professors who will act in basic education, mainly in this stage that goes of 1º to 5º year.
Keywords: game; initial series; learning